Mechanisms of post-transcriptional gene regulation in bacterial biofilms - Vadyvaloo, Viveka; Martínez, Luary (Frontiers in Cellular and Infection Microbiology, 2014)
Abstract Biofilms are characterized by a dense multicellular community of microorganisms that can be formed by the attachment of bacteria to an inert surface and to each other. The development of biofilm involves the initial attachment of planktonic bacteria to a surface, followed by replication, cell-to-cell adhesion to form microcolonies, maturation and detachment. Mature biofilms are embedded in a self-produced extracellular polymeric matrix composed primarily of bacterial-derived exopolysaccharides, specialized proteins, adhesins and occasionally DNA. Because the synthesis and assembly of biofilm matrix components is an exceptionally complex process, the transition between its different phases requires the coordinate expression and simultaneous regulation of many genes by complex genetic networks involving all levels of gene regulation. The finely controlled intracellular level of the chemical second messenger molecule, cyclic-di-GMP is central to the post-transcriptional mechanisms governing the switch between the motile planktonic lifestyle and the sessile biofilm forming state in many bacteria. Several other post-transcriptional regulatory mechanisms are known to dictate biofilm development and assembly and these include RNA-binding proteins, small non-coding RNAs, toxin-antitoxin systems, riboswitches and RNases. Post-transcriptional regulation is therefore a powerful molecular mechanism employed by bacteria to rapidly adjust to the changing environment and to fine tune gene expression to the developmental needs of the cell. In this review, we discuss post-transcriptional mechanisms that influence the biofilm developmental cycle in a variety of pathogenic bacteria.